Shedding light on host niches: label‐free in situ detection of Mycobacterium gordonae via carotenoids in macrophages by Raman microspectroscopy. (24th January 2015) - Silge, Anja; Abdou, Elias; Schneider, Kilian; Meisel, Susann; Bocklitz, Thomas; Lu‐Walther, Hui‐Wen; Heintzmann, Rainer; Rösch, Petra; Popp, Jürgen
Summary Macrophages are the primary habitat of pathogenic mycobacteria during infections. Current research about the host–pathogen interaction on the cellular level is still going on. The present study proves the potential of Raman microspectroscopy as a label‐free and non‐invasive method to investigate intracellular mycobacteria in situ. Therefore, macrophages were infected with Mycobacterium gordonae, a mycobacterium known to cause inflammation linked to intracellular survival in macrophages. Here, we show that Raman maps provided spatial and spectral information about the position of bacteria within determined cell margins of macrophages in two‐dimensional scans and in three‐dimensional image stacks. Simultaneously, the relative intracellular concentration and distributions of cellular constituents such as DNA, proteins and lipids provided phenotypic information about the infected macrophages. Locations of bacteria outside or close to the outer membrane of the macrophages were notably different in their spectral pattern compared with intracellular once. Furthermore, accumulations of bacteria inside of macrophages exhibit distinct spectral/molecular information because of the chemical composition of the intracellular microenvironment. The data show that the connection of microscopically and chemically gained information provided by Raman microspectroscopy offers a new analytical way to detect and to characterize the mycobacterial infection of macrophages.